Hatha yoga is more effective in improving kinesiophobia and subjective well-being when combined with self-compassion meditation in people with CLBP: a randomized control trial - De Giorgio, Andrea; Angilletta, Sonia; Matteo, Barbara; Bonavolontà, Valerio; Bragazzi, Nicola Luigi; Kuvačić, Goran (Frontiers in Psychology, 2023)
Objective: The present study aims to examine whether combining hatha yoga practice with selfcompassion meditation could influence kinesiophobia, emotions, perceived stress, and perceived disability among individuals with chronic low back pain when compared with hatha yoga alone.The randomized controlled study included 70 participants with chronic low back pain (CLBP) who were randomly assigned to a Hatha yoga group (HY; n=35) or a Hatha yoga group plus self-compassion meditation (HYSCM; n=35). Participants followed a protocol for 8 weeks, and the assessments were carried out before and after the intervention, with a follow-up evaluation conducted after one month. The participants completed the PANAS, PSS, TSK, and RMQ questionnaires. A Generalized Estimating Equation was used to explore the effect of interventions.Results: Both HY and HYSCM groups improved kinesiophobia, perceived disability, and stress at the follow-up. However, the HYSCM group shown a more significant reduction in kinesiophobia compared to the HY group. Moreover, significant improvement in positive affect and a reduction in negative affect over time in the HYSCM group were observed.Hatha yoga practice when combined with self-compassion meditation led to extra benefits by exhibiting a prolonged effect, especially on kinesiophobia positive and negative effects.